1991
DOI: 10.1259/0007-1285-64-764-734
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a Microselectron HDR iridium 192 source

Abstract: A method for the calibration of the output, in terms of an air kerma rate, of the high activity miniature iridium 192 sources used in the Microselectron HDR afterloading unit is described. An air kerma rate is measured using a calibrated thimble chamber in an "in-air" calibration jig. The results are compared with an air kerma rate derived from the manufacturer's test certificate. In some cases, the ionization chamber measurements have been followed by a further calibration check using thermoluminescent dosime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Some studies use a calibration factor from irradiation with 60 Co (Kapp et al 1992, Pradhan andQuast 2000) or a 300 kVp clinical orthovoltage therapy beam (Howlett et al 1996, Duggan et al 2000. For example, Flynn and Workman (1991) discussed the problems involved in measuring the air kerma rate at 5 cm from low dose rate (LDR) and HDR 192 Ir brachytherapy sources, such as the steep dose gradient, electrometer leakage over long exposure times for ionization chambers (for LDR sources) and that it would be preferable to have a calibration factor for the relevant photon energy traceable to a standard rather than using a factor for 60 Co. Furthermore, Mangold et al (2001) stated that the limited accuracy of source strength specification of 192 Ir is a possible source of a systematic error in the treatment planning calculation since it is an essential input parameter.…”
Section: Diagnostic and Interventional Radiologymentioning
confidence: 99%
“…Some studies use a calibration factor from irradiation with 60 Co (Kapp et al 1992, Pradhan andQuast 2000) or a 300 kVp clinical orthovoltage therapy beam (Howlett et al 1996, Duggan et al 2000. For example, Flynn and Workman (1991) discussed the problems involved in measuring the air kerma rate at 5 cm from low dose rate (LDR) and HDR 192 Ir brachytherapy sources, such as the steep dose gradient, electrometer leakage over long exposure times for ionization chambers (for LDR sources) and that it would be preferable to have a calibration factor for the relevant photon energy traceable to a standard rather than using a factor for 60 Co. Furthermore, Mangold et al (2001) stated that the limited accuracy of source strength specification of 192 Ir is a possible source of a systematic error in the treatment planning calculation since it is an essential input parameter.…”
Section: Diagnostic and Interventional Radiologymentioning
confidence: 99%
“…Source calibration has received much attention from medical physicists and the medical literature contains many discussions about its technical aspects (Flynn and 161 NuREG/CR-6 125 Workman, 1991;Goetsch et al, 1991;Kohn, Gooch, and Zajac, 1991;Meertens, 1990;Wu et al, 1990). Problems have been reported that have implicated inaccurate supplier source calibration data.…”
Section: Quality Assurance and Maintenancementioning
confidence: 99%
“…The calibration of an Ir-192 HDR system using the Farmer chamber has been studied for decades [ 8 12 ]. The standard AKS calibration for Ir-192 sources was established at the University of Wisconsin Accredited Dosimetry Calibration Laboratory (UWADCL) in 1991 by Goetsch et al [ 9 ], who employed an interpolation procedure using NIST calibrations of 662 keV (Cs-137) and 146 keV (250 kVcp X-rays) to get a calibration of 397 keV (the exposure-weighted average Ir-192 energy) because NIST does not offer calibration of ionization chambers with the gamma-ray spectrum of Ir-192.…”
Section: Introductionmentioning
confidence: 99%